The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fneur.2020.00792
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Pain Assessment Tools for Use in People Living With Stroke: Systematic Review

Abstract: Background: Pain is a common problem after stroke and is associated with poor outcomes. There is no consensus on the optimal method of pain assessment in stroke. A review of the properties of tools should allow an evidence based approach to assessment. Objectives: We aimed to systematically review published data on pain assessment tools used in stroke, with particular focus on classical test properties of: validity, reliability, feasibility, responsiveness. Methods: We searched multiple, cross-disciplinary dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Among pain intensity assessment tools, the most commonly used assessment tool is the Faces Pain Scale, which has the most supporting evidence demonstrating that it is an effective means to assess patients’ pain (Edwards et al., 2020). In this study, we used schematic facial depictions to show varying degrees of discomfort in stroke patients and different facial images constitute the Wong‐Baker FACES Pain Rating Scale (WBS).…”
Section: The Studymentioning
confidence: 99%
“…Among pain intensity assessment tools, the most commonly used assessment tool is the Faces Pain Scale, which has the most supporting evidence demonstrating that it is an effective means to assess patients’ pain (Edwards et al., 2020). In this study, we used schematic facial depictions to show varying degrees of discomfort in stroke patients and different facial images constitute the Wong‐Baker FACES Pain Rating Scale (WBS).…”
Section: The Studymentioning
confidence: 99%
“…The possible clinical implications of lower pain tolerance have particular importance in stroke patients, considering the co‐occurrence of aphasia and cognitive decline that render many of these patients with limited ability to communicate their pain (Edwards et al, 2020). If stroke patients are more sensitive to pain, or have more difficulty coping with it, this calls for awareness in health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…One was the above-mentioned systematic review by de Vries et al 9 and the other was a systematic review by Edwards et al 14 However, the focus of these reports differs from our scoping review. Of the various communication problems, de Vries et al 9 focused solely on aphasia, while Edwards et al 14 did not focus on any communication problems. Further, de Vries et al 9 included studies with proxy pain ratings, whereas our scoping review focuses solely on patient self-report.…”
Section: Introductionmentioning
confidence: 95%
“…A preliminary search of PROSPERO, MEDLINE, CINAHL, the Cochrane Database of Systematic Reviews, and JBI Evidence Synthesis was conducted, and while no scoping reviews were identified, the search yielded two systematic reviews regarding pain assessment instruments for the diagnosis of pain in people who have had a stroke. One was the above-mentioned systematic review by de Vries et al 9 and the other was a systematic review by Edwards et al 14 However, the focus of these reports differs from our scoping review. Of the various communication problems, de Vries et al 9 focused solely on aphasia, while Edwards et al 14 did not focus on any communication problems.…”
Section: Introductionmentioning
confidence: 95%